A beginners guide to Sf9 and Sf21 insect cell line culture and troubleshooting - Joanna Kwiatkowska; Ewa Stein; Anastasiia Romanenko; Martyna Plens-Gałąska; Małgorzata Podsiadła-Białoskórska; Ewa Szołajska; Uwe Kühn; Kinga Kamieniarz-Gdula (Scientific Reports)
Abstract Recombinant proteins are not only a crucial research tool but are also widely implemented in biomedicine. There are a number of expression systems used for recombinant protein production. Among them Spodoptera frugiperda (Sf) insect cell system is a powerful tool for multiprotein expression. Most commonly used are Sf9 and Sf21 cell lines due to their cost-effectiveness and availability. While a collection of protocols describing the Sf cell lines culturing is available, we have found them incomplete and their adaptation to real laboratory conditions challenging. Here we created a user-friendly hands-on protocol suitable for beginners. Our work combines the efforts of three independent laboratories which culture Sf cells, two labs with long experience, and one which recently successfully set up this system from scratch. We propose novel tricks and tips that allow for culturing of healthy Sf cells, and high protein yield production. Besides catering for beginners, our protocol can serve as a troubleshooting guide for more experienced researchers. We believe that this work is useful for biochemistry all the way to biomedical laboratories. Starting with an exhaustive description of Sf cell lines, through baculovirus expression vector system characteristic, this publication is a protocol, troubleshooting guide and compendium in one.